2019
DOI: 10.1111/jfpp.14326
|View full text |Cite
|
Sign up to set email alerts
|

Quality preservation and safety ensurement of a vegetable smoothie by high‐pressure processing

Abstract: This research aims to evaluate the effect of a previously optimized high‐pressure processing (HPP) treatment on the vegetable smoothie stability during 28 days at 5 °C and on the inactivation of a contamination with Listeria monocytogenes and Escherichia coli O157:H7 surrogates during 12 days at 15 °C. HPP (630 MPa/6 min) reduced native microbiota to values below detection limit (DL = 1 log CFU/g) and significantly reduced polyphenol oxidase, peroxidase, and pectin methylesterase initial activities (16.7%, 29.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Many earlier studies also report the significant occurrence of, e.g., enterobacteria in smoothie drinks at levels of 1.9 log CFU/mL [ 32 ], 2.4 log CFU/mL [ 33 ], 3.39 log CFU/mL [ 34 ] and even 5.5 log CFU/mL [ 35 ]. The analysis of ten smoothie samples purchased in the Czech Republic revealed the presence of coliform bacteria in the range of 1.5–6.0 log CFU/mL, which basically corresponds to previously published results of studies from Argentina and Spain [ 32 , 33 , 35 ]. Enterobacter bugandensis , Klebsiella variicola and Klebsiella pneumoniae were among the most frequently detected representatives of coliform bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Many earlier studies also report the significant occurrence of, e.g., enterobacteria in smoothie drinks at levels of 1.9 log CFU/mL [ 32 ], 2.4 log CFU/mL [ 33 ], 3.39 log CFU/mL [ 34 ] and even 5.5 log CFU/mL [ 35 ]. The analysis of ten smoothie samples purchased in the Czech Republic revealed the presence of coliform bacteria in the range of 1.5–6.0 log CFU/mL, which basically corresponds to previously published results of studies from Argentina and Spain [ 32 , 33 , 35 ]. Enterobacter bugandensis , Klebsiella variicola and Klebsiella pneumoniae were among the most frequently detected representatives of coliform bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…In general, HPP has been shown to have minor or no significant effect on micronutrients [ 149 ] and on total the carotenoid content within vegetable matrices [ 150 ]. In general, HPP treatments below 50 °C caused no degradation of ascorbic acid in fruit preparation products [ 134 , 135 , 141 , 142 , 151 , 152 ]. Regarding total flavonoids, there are contradictory results: Nayak et al [ 133 ] reported the decrease of these compounds was less after pressurization, in comparison to heated samples; other work reported a similar decrease after storage in both HPP and thermal processing samples [ 96 ]; and Vieira et al [ 137 ] showed that HPP caused a decrease of 39.3%.…”
Section: Impact Of Hpp On Antioxidant Activity During Storage Of Fruits and Fruit Productsmentioning
confidence: 99%
“…Fernández et al [ 151 ] formulated a smoothie with the following composition (weight): orange juice (59%), apples (15%), carrots (15%), beet leaves (6%), and beet stems (5%), which was treated with HPP (630 MPa for 6 min). Initially, HPP-treated samples presented higher values of ascorbic acid and total phenolics (about 7%) than in the control ones, and then a decrease took place with the storage time for both type of smoothies.…”
Section: Impact Of Hpp On Antioxidant Activity During Storage Of Fruits and Fruit Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to thermal treatment, HP was found to keep the visual color much closer to that of the untreated smoothie [ 21 ]. While thermal pasteurization (P) could negatively affect the stability of the BACs in smoothies [ 22 ], a recent study showed that HP could even increase the baseline levels of nutritional quality in vegetable smoothies during cold storage [ 23 ]. Moreover, HP was found to be a less destructive treatment in terms of the vitamin C stability, compared to thermal processing, which could reduce vitamin C content by 35–44% [ 24 ].…”
Section: Introductionmentioning
confidence: 99%